Has OMP legislation been successful? Yes, though the orphan drug market remains immature - Oriol Solà-Morales (Taylor & Francis Group, 2019)
Incentives for the development of Orphan Medicinal Products (OMP) development have been introduced in both the European Union and the US, yet there has been a relatively little investigation of the success of these policies. An in-depth analysis of the EU market has not been performed, neither in terms of access nor, especially, in terms of the industrial consequences. In order to provide potential measures of success of the OMP program in Europe, we have assessed the levels of OMP designation/approval by EMA and the financial performance of the manufacturing companies during the 5-year period between 2011 and 2015. Of the 1706 products that were granted an OMP designation by EMA during this period, only 138 products (8,1%) reached the market. These products were generally developed by small to medium enterprises (SMEs). In comparison to more mature companies with broader portfolios, these OMP-SMEs are more vulnerable to economic failure due to proportionally higher R&D investment costs, higher sales costs and more limited access to cash at preferential rates. The cost development and their lack of cash availability pout them at financial stake. While this legislation has been effective in creating access to OMP designation, patients are very highly unlikely to benefit from these developments, often because of non-clinical issues: the marketplace is still immature, and companies are still financially vulnerable. Financial and non-financial incentives will be critical to allow OMP products to reach the market, so that a fully functioning and competitive market can be established.